Challenges prescribing and dispensing oral antibiotics with poor palatability for paediatric patients: A qualitative interview study with GPs and pharmacists - Ayat Elgammal; Joseph Ryan; Colin Bradley; Abina Crean; Margaret Bermingham (Elsevier, 2025)
Background: Poor palatability of antibiotics is a key cause for non-adherence to antibiotic treatment among children. Failure to complete antibiotic treatment because of poor palatability can cause disease recurrence and may contribute to increasing rates of antimicrobial resistance. The aim of this study was to investigate the experience and challenges faced by general practitioners (GPs) and community pharmacists regarding prescribing and dispensing oral liquid antibiotics for children and the impact of poorly palatable antibiotic formulations on patients and the health-system. Methods: One-to-one semi-structured interviews with GPs and pharmacists were conducted via an online video-conferencing platform. Data were analysed using thematic analysis. Results: Twenty participants (7 GPs and 13 pharmacists) were interviewed. Three main themes and eight subthemes were identified. Theme 1: challenges reported by GPs and pharmacists included four subthemes; (i) factors affecting prescribing and dispensing antibiotics, (ii) reasons to select poorly palatable antibiotics, (iii) palatability discussion with parents, and (iv) formulation factors affecting oral liquid antibiotic acceptability. Theme 2: the impact of prescribing or dispensing poorly palatable oral liquid antibiotics encompassed two sub themes; (i) patient impact and (ii) health-system impact. Theme 3: overcoming palatability challenges involved two subthemes; (i) raising awareness of flavour and palatability issues among healthcare professionals and (ii) counselling parents while prescribing and before dispensing. Conclusions: There is a need to increase palatability awareness among healthcare professionals and parents. The development of more palatable oral liquid formulations can play a role in improving prescribing and medicines taking practices.